25x-7-15x+3=

Simple and best practice solution for 25x-7-15x+3= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 25x-7-15x+3= equation:


Simplifying
25x + -7 + -15x + 3 = 0

Reorder the terms:
-7 + 3 + 25x + -15x = 0

Combine like terms: -7 + 3 = -4
-4 + 25x + -15x = 0

Combine like terms: 25x + -15x = 10x
-4 + 10x = 0

Solving
-4 + 10x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4' to each side of the equation.
-4 + 4 + 10x = 0 + 4

Combine like terms: -4 + 4 = 0
0 + 10x = 0 + 4
10x = 0 + 4

Combine like terms: 0 + 4 = 4
10x = 4

Divide each side by '10'.
x = 0.4

Simplifying
x = 0.4

See similar equations:

| 7x-3(6x+8)=9 | | (5x-17)=9 | | -2505-100= | | 25x-7-15x+3=20x-6-10x+14 | | f=2(9a)-3(3a)+4 | | 1.74x+3.26(19-x)=19*2 | | 1.74x+3.26(19-x)=19 | | f=2(9)-3(3)+4 | | -3w-6w+3=0 | | .66y-6=12 | | x^4-5x=0 | | x+(x-2)+2x=26 | | -.5x+.75=87.5 | | b^2-b=72 | | y-1=5(x+2) | | -0.8x-6.4=14.4 | | -0.8x-6.6=14.4 | | 9(4x-9)+10= | | 4b=56 | | 6(x-2)=3-(x+1) | | .66x-6=.5x+8 | | 1.5y=1200 | | 2x+4.5(37-x)=119 | | (3x^2)dx-(5y^4)dy=0 | | 3x+4x-x= | | 7x+5-1.3x=46-.3x | | -10=120 | | 5(24x+11)=8x-15 | | (-6-5i)(-3-5i)= | | y[n]=0.25x[n]+0.25x[n+1]+0.25x[n-1]+0.25x[n+2] | | 3c-24=51 | | 2.2(x-4)+5x=7 |

Equations solver categories